Detection of Municipal Efficiency Patterns and Unusual Practises by Data Analysis of Public Budgets - Vinkler, Vladimír; Zouhar, Jan, 1982-; Holý, Vladimír; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis examines the efficiency of Czech municipalities in transforming financial resources into positive demographic and socioeconomic outcomes. Using Data Envelopment Analysis (DEA) with Variable Returns to Scale, the study evaluates 6,244 municipalities across the Czech Republic over the period 2010-2023. The research integrates comprehensive finan- cial data from municipal budgets with demographic statistics and debt enforcement records to identify patterns of municipal performance. Through spatial analysis and visualization techniques, including choropleth mapping, the study reveals regional disparities in efficiency. The findings indicate that efficient municipalities maintain lower operational expenses, allo- cate more resources to investment rather than operations, sustain healthier budget balances, and achieve better demographic outcomes, including population growth and lower rates of debt enforcement proceedings. The research identifies both exemplary performers through superefficiency analysis and specific municipal characteristics associated with inefficiency, such as tourism dependence and peripheral geographical location. This research contributes to understanding how municipal financial management practices influence local demographic development and offers a methodological framework for identifying unusual financial practices in public administration.
Vedoucí práce: Jan Zouhar
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analytics [obor bakal. práce]; bakalářské práce; bachelor's theses